2018
DOI: 10.1002/ijc.31739
|View full text |Cite
|
Sign up to set email alerts
|

A novel tumor‐based epithelial‐to‐mesenchymal transition score that associates with prognosis and metastasis in patients with Stage II/III colorectal cancer

Abstract: It is increasingly appreciated that host factors within the tumor center and microenvironment play a key role in dictating colorectal cancer (CRC) outcomes. As a result, the metastatic process has now been defined as a result of epithelial-mesenchymal transition (EMT). Establishment of the role of EMT within the tumor center and its effect on the tumor microenvironment would be beneficial for prognosis and therapeutic intervention in CRC. The present study assessed five immunohistochemical EMT markers within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 36 publications
(93 reference statements)
3
26
0
1
Order By: Relevance
“…Previous studies indicate that stimulating EMT and increasing CSCs can promote cancer metastasis and relapse . Cells undergoing EMT are known to acquire stem cell‐like properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that stimulating EMT and increasing CSCs can promote cancer metastasis and relapse . Cells undergoing EMT are known to acquire stem cell‐like properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that stimulating EMT and increasing CSCs can promote cancer metastasis and relapse. 34,[47][48][49][50] Cells undergoing EMT are known to acquire stem cell-like properties. Loss of epithelial marker E-cadherin, increased expression of mesenchymal markers Fibronectin and Vimentin and the EMT regulator Snail, which are important events in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic features of EMT are the decreased expression of the cell adhesion molecule, E-cadherin (E-Cad), and the enhanced expression of the mesenchymal marker, Vimentin (VIM) [19,20]. Previous studies have demonstrated that EMT is a vital process in tumor progression and metastasis, and is associated with a poor prognosis and tumor aggressiveness in several human epithelial cancers, including GC [21][22][23][24]. The identification of factors that induce EMT would greatly contribute to understanding the mechanisms of invasion and metastasis in GC, and may aid the development of effective approaches for the prevention and therapy of this malignancy.…”
Section: Ivyspringmentioning
confidence: 99%
“…This may be related to the fact that PanCk demonstrates all the epithelial cell clusters (including necrotic fragments), whereas ITGB4 is more specific for invasive cells (when present in small cell clusters) and is involved in EMT , a phenomenon to which tumour budding is at least partly related . For this reason, it is tempting to hypothesise that biomarkers linked with EMT, which have also shown correlation with survival , might be relevant additional markers of tumour budding in challenging tumour specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Slik et al present in small cell clusters) and is involved in EMT [34], a phenomenon to which tumour budding is at least partly related [4]. For this reason, it is tempting to hypothesise that biomarkers linked with EMT, which have also shown correlation with survival [35], might be relevant additional markers of tumour budding in challenging tumour specimens. EMT is a phenomenon consisting of loss or aberrant expression of adherence junction E-cadherin, disintegration of tight junctions (ZO-1), and of basement membranes (ITGB4).…”
mentioning
confidence: 99%